Let's talk business: The language recruiters use to attract STEM graduates. Issue 2 (April 2020) - Pearl, Alastair O.; Orlando, Laurence; Larson, Ian; Rayner, Gerry M.
The last decade has seen a shrinking of degree-level employment opportunities for young people (aged under 24 years) in Australia and globally. This research aims to better understand the job advertisements to which our graduates are exposed. This article presents a universal method to collect and process advertisements from an online job board. Two million job advertisements were extracted, cleaned, processed and reviewed to highlight the uses of Bloom's Taxonomy ('evaluate' and 'create' levels) and critical thinking (CT) words within them. The study looked at those advertisements of interest to Bachelor of Pharmaceutical Science graduates in Australia. Analyses indicate that the use of these words is not dependent on the size of the company, the salary of the advertised position, job permanency or specific industry. However, Bloom's Taxonomy words were used to a much greater extent than CT words, potentially reflecting the lack of a clear and coherent definition and conceptualisation of CT skills in industry. The authors encourage increased collaboration and discussion between institutions and industry to define and articulate the skills graduates require.